IMPLEMENTASI MODEL LATIHAN MODIFIKASI GERAK UNTUK MENINGKATKAN TENDANGAN MAWASHI GERI SHORINJI KEMPO - Anak Agung Ngurah Putra Laksana (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
This study aims to improve the mawashi geri technique skills by modifying the movements of the kempo branch of beginner kenshi Dojo Mahadewa University.This research was carried out in the Dojo Mahadewa University, with the subject of a kenshi study aged 20-23 years. This research method is an action research method using observation and observation techniques with a research cycle. The design of this study with each cycle consisting of planning, implementation, observation/evaluation and reflection. The subjects of this study were Kenshi Dojo Mahadewa University as many as 30 people. Based on the results of the Dojo Mahadewa University research on the initial test that entered the graduation standard only 6 kenshi and who did not enter the graduation standard was 24 kenshi so the percentage of passing on the initial test was 20%. Whereas in the first cycle the entry standards were 16 kenshi and those not included in the 14 kenshi graduation standard so the percentage of graduation increased to 53,3%. In the second cycle all kenshi entered into the graduation standard of 30 kenshi and the percentage of graduation reached the target of 100%. Thus the exercise using motion modification can improve the technique of mawasi geri on kenshi beginners  Dojo Mahadewa University. Keyword : Modified motion, Mawashi Geri , Shorinji Kempo.